(untitled) (Research, Society and Development, 2024)
Immunology topics are complex and of great importance in the academic training of undergraduates in the health field, and unconventional methodologies are highly relevant tools to help with learning and retention. Thus, the objective of this study is to demonstrate the use of active methodologies in teaching immunology to university students studying Nutrition and Biological Sciences, Campus Rio Paranaíba, Federal University of Viçosa. During the pandemic period, in 2021, Covid-19 issues were worked on using music and mental maps. The students listened to the ASAS song prepared by the subject teacher and did activities related to the theme, such as answering questions, essays and drawings with the music theme. In the class on the immunological synapse, students made drawings to illustrate the subject. At the end of the course, students created a mind map in pairs on the Canva platform. In 2022, with the return of in-person activities, the themes of immunological synapses and serums and vaccines were worked on using the woodcut technique. The majority of students carried out the activities proposed with the drawings and strings, with some reporting that these works generate knowledge and fix the content, in addition to working on the artistic side of such complex themes. It is concluded that unconventional active methodologies were effective in generating knowledge and its retention, in addition to stimulating artistic creation by students.